Deliberative mini-publics : core design features - Curato, Nicole (Bristol shorts research., 2021)
Bringing together ten leading researchers in the field of deliberative democracy, this important book examines the features of a Deliberative Mini-Public (DMP) and considers the contributions that DMPs can make not only to the policy process, but also to the broader agenda of revitalising democracy in contemporary times.